The Distribution and Localization of Collagen Triple Helix Repeat Containing-1 in Naturally and Experimentally Avian Leukosis Virus Subgroup J-Infected Chickens - Pang, Yu; Zhou, Defang; Zhou, Jing; Xue, Jingwen; Wang, Yiya; Cheng, Ziqiang (Frontiers in Veterinary Science, 2020)
Collagen triple helix repeat containing-1 (CTHRC1) has recently been identified as avian leukosis virus subgroup J (ALV-J) replication-dependent factor that remarkably facilitates ALV-J replication via interaction with the envelope glycoprotein (SU) of ALV-J. However, the dynamic distribution and localization of CTHRC1 in various tissues upon ALV-J infection are still unknown. In this study, data revealed that the levels of CTHRC1 were significantly increased in various tissues and that the protein was mainly located in the cytoplasm and nucleus of parenchymal cells in tissues of chickens that were infected by ALV-J naturally and experimentally. Interestingly, CTHRC1 was also observed in leukocytes other than erythrocytes in congested veins of ALV-J-infected tissues. Consequently, the positive cells in these veins were confirmed as lymphocytes by laser confocal microscopy. Taken together, these results conclude that the CTHRC1 is an inducible protein and exhibited ubiquitous expression in ALV-J-infected chickens, which may provide basic information for in-depth study of ALV-J infection and replication mechanisms.